Knife skills in the kitchen - Trotter, Charlie; Wareing, Marcus; Hill, Sahun; Hall, Lyn (New York, NY Dorling Kindersley., 2008)
Teaches knifing techniques for preparing meat, vegetables, herbs, and other foods, with illustrations and step-by-step instructions, plus information about knives used by chefs around the world.
Keywords: Knives; Cutting; Cooking